Cognitive performance in distinct groups of children undergoing epilepsy surgery-a single-centre experience - Benova, Barbora; Belohlavkova, Anezka; Jezdik, Petr; Jahodová, Alena; Kudr, Martin; Komarek, Vladimir; Novak, Vilem; Liby, Petr; Lesko, Robert; Tichý, Michal; Kyncl, Martin; Zamecnik, Josef; et al. (PeerJ, 2019)
BACKGROUND: We aimed first to describe trends in cognitive performance over time in a large patient cohort (n = 203) from a single tertiary centre for paediatric epilepsy surgery over the period of 16 years divided in two (developing-pre-2011 vs. established-post-2011). Secondly, we tried to identify subgroups of epilepsy surgery candidates with distinctive epilepsy-related characteristics that associate with their pre- and post-surgical cognitive performance. Thirdly, we analysed variables affecting pre-surgical and post-surgical IQ/DQ and their change (post- vs. pre-surgical). METHODS: We analysed IQ/DQ data obtained using standardized neuropsychological tests before epilepsy surgery and one year post-surgically, along with details of patient's epilepsy, epilepsy surgery and outcomes in terms of freedom from seizures. Using regression analysis, we described the trend in post-operative IQ/DQ. Cognitive outcomes and the associated epilepsy- and epilepsy surgery-related variables were compared between periods before and after 2011. Using multivariate analysis we analysed the effect of individual variables on pre- and post-operative IQ/DQ and its change. RESULTS: Epilepsy surgery tends to improve post-surgical IQ/DQ, most significantly in patients with lower pre-surgical IQ/DQ, and post-surgical IQ/DQ strongly correlates with pre-surgical IQ/DQ (Rho = 0.888, p < 0.001). We found no significant difference in pre-, post-surgical IQ/DQ and IQ/DQ change between the periods of pre-2011 and post-2011 (p = 0.7, p = 0.469, p = 0.796, respectively). Patients with temporal or extratemporal epilepsy differed in their pre-surgical IQ/DQ (p = 0.001) and in IQ/DQ change (p = 0.002) from those with hemispheric epilepsy, with no significant difference in post-surgical IQ/DQ (p = 0.888). Groups of patients with different underlying histopathology showed significantly different pre- and post-surgical IQ/DQ (p < 0.001 and p < 0.001 respectively) but not IQ/DQ change (p = 0.345).Variables associated with severe epilepsy showed effect on cognitive performance in multivariate model. DISCUSSION: Post-surgical IQ/DQ strongly correlates with pre-surgical IQ/DQ and greatest IQ/DQ gain occurs in patients with lower pre-surgical IQ/DQ scores. Cognitive performance was not affected by changes in paediatric epilepsy surgery practice. Pre- and post-operative cognitive performances, as well as patients' potential for cognitive recovery, are highly dependent on the underlying aetiology and epileptic syndrome.
Keywords: Cognitive outcome; Long-term epilepsy-associated tumours; Malformations of cortical development; Paediatric epilepsy surgery; Drug resistant epilepsy